HEPARINOID-BASED BIOMATERIALS AND THEIR APPLICATIONS - MASAYUKI ISHIHARA; SATOKO KISHIMOTO; KAORU MURAKAMI; HIDEMI HATTORI; SHINGO NAKAMURA (International Journal of Pharma and Bio Sciences, 2016)
Heparin, heparan sulfate (HS), heparin-like molecules from animal or plant origins, and synthetic derivatives of sulfated polysaccharides are referred to heparinoids. The various biological activities of heparinoids are generally ascribed to their specific interaction with heparin-binding proteins such as growth factors (GFs) and extracellular matrix (ECM) biomolecules, mediated by specific domains with distinct saccharide sequences. The specific interactions of heparinoids with GFs or ECM biomolecules require different combinations of sulfated groups, and thus, require different highly sulfated saccharide sequences. Multivalent and cluster effects of heparinoids are also important factors that control their interactions and biological activities. In this review, we describe heparinoid-based biomaterials to offer novel means to engineer functional protein delivery systems for biomedical applications